1995
DOI: 10.1063/1.1146164
|View full text |Cite
|
Sign up to set email alerts
|

An insert for single-molecule magnetic-resonance spectroscopy in an external magnetic field

Abstract: Articles you may be interested inSimultaneous measurements of heat capacity and spinlattice relaxation time in high magnetic field at low temperature Rev.A sensitive capacitance thermometer at low temperature for use in magnetic fields up to 20 T Rev.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Typically, fluorescence-excitation spectra of an individual complex are obtained in rapid succession by scanning the laser repetitively through the spectral range of interest and storing the individual traces separately in computer memory. Details about the experimental setup can be found in Van der Meer et al (1995) and Hofmann et al (2004b).…”
Section: Methodsmentioning
confidence: 99%
“…Typically, fluorescence-excitation spectra of an individual complex are obtained in rapid succession by scanning the laser repetitively through the spectral range of interest and storing the individual traces separately in computer memory. Details about the experimental setup can be found in Van der Meer et al (1995) and Hofmann et al (2004b).…”
Section: Methodsmentioning
confidence: 99%
“…Next, the sample was mounted into a home‐built cryogenic insert which also accommodated the microscope objective (NA, numerical aperture = 0.90, Microthek, Hamburg, Germany). The insert was based on a mechanical arrangement, described previously by van der Meer et al . (1995), that allows in situ adjustments of the objective and sample with respect to each other along two mutually orthogonal directions (focus and sample position) with submicrometre precision.…”
Section: Methodsmentioning
confidence: 99%
“…When slightly tilted around either hinge, the lens-mirror holder also shifts in the sample plane. Our group has previously shown that flexure hinges provide reliable and stable positioning in low-temperature microscopy (27,28).…”
Section: Inside the Cryostatmentioning
confidence: 99%